Evaluating the effect of transport infrastructure on the employment in Vietnam - Zhen Yu; To Boi Luu (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2022)
During the process of international economic integration, the labor issue plays a vital, urgent, and long-term role in the sustainable development of the economy. The impact of employment on a country's investment decisions is significant. The material underpinning of a nation's socio-economic growth is its transport infrastructure. The impact of infrastructure upgrades on employment in Vietnam's economic sectors is the focus of this article. Furthermore, the study investigates whether the Vietnamese government's annual investment in infrastructure development benefits employees as projected (using data from the Vietnam General Statistics Office (VNGSO) for 19 economic sectors from 2005 to 2019). The results of the System Generalized Method of Moments (System-GMM) show that improving the quality of transport infrastructure can significantly increase employment rates in different sectors. The data show that transport infrastructure plays a key role in ensuring smooth connectivity of the entire national, regional and local economies. It reduces transport costs and facilitates the mobility of workers.JEL Classification J8; L91; O18